A afetividade da relação pedagógica na gestão de comportamentos em contexto de jardim de infância - Lacerda, Maria Magalhães Ramalho de Andrade e Sousa Pereira de (2025)
This investigation focuses on a reflection on affectivity in the pedagogical relationship and its role in behavior management in educational contexts, addressing the role of the early childhood educator in this process. The study was conducted within the framework of supervised practice in a kindergarten classroom, with a group composed of 25 children. The study addresses three guiding questions: (i) how can the educator create affective and trusting relationships with children; (ii) what strategies can the educator implement to promote group cohesion, participation, and affective relationships in order to prevent situations of indiscipline; (iii) what strategies can the educator use to deal with disruptive behaviors? A qualitative methodology was employed, using techniques such as observation and data collection instruments, including field notes and an interview conducted with the classroom educator. The results showed the importance of the educator's competence in emotionally self-regulating in order to support the child in developing the same competencies and in solving behavioral problems, and having embedded in their practice the appropriate strategies to deal with challenges that may arise. In this regard, the need for continuous reflection by the educator is also highlighted, as well as training, so that they have intentionality in their educational practice, supported by what research presents to us as strategies that promote the child's best development. Empathy also proves to be fundamental as a means to better understand the origin of the child's behaviors and thus be able to adapt strategies to their affective needs. Finally, the study demonstrates that behavior management is more effective when the educator invests in promoting participation, group autonomy, and affective relationships among children, which in turn promote emotional, social, and behavioral self-regulation competencies. Keywords: